Pendampingan Dan Pelatihan Baca Tulis Pegon Untuk Memudahkan Anak Memaknai Kitab Di Madrasah Diniyah Sabilal Muhtadin Di Ds. Pulorejo Kec. Ngoro Kab. Jombang - Wirda Lailatul Muqtadiroh; Miksan Ansori (LP3M IAIFA Kediri, 2021)
Arabic pegon, which is an Arabic writing, script or letter without symbols or punctuation or sound. In the Javanese-Indonesian dictionary, pegon means unusual to pronounce. Another word for